
3个回答
展开全部
(a^m+1*b^n+2)(a^2n-1*b^2m)=a^(m+1+2n-1)*b^(n+2+2m)=a^5*b^3
所以m+1+2n-1=5,
n+2+2m=3,
解得m=-1
n=3
m+n=2.
所以m+1+2n-1=5,
n+2+2m=3,
解得m=-1
n=3
m+n=2.
展开全部
(a^m+1*b^n+2)(a^2n-1*b^2m)=a^(m+1+2n-1)*b^(n+2+2m)=a^5*b^3
所以m+1+2n-1=2,
n+2+2m=3,
解得m=0
n=1
m+n=1.
所以m+1+2n-1=2,
n+2+2m=3,
解得m=0
n=1
m+n=1.
已赞过
已踩过<
评论
收起
你对这个回答的评价是?
展开全部
(a^m+1*b^n+2)(a^2n-1*b^2m)=a^(m+1+2n-1)*b^(n+2+2m)=a^5*b^3
∴m+1+2n-1=5
n+2+2m=3
解得:m=-1
n=3
m+n=-1+3=2
∴m+1+2n-1=5
n+2+2m=3
解得:m=-1
n=3
m+n=-1+3=2
已赞过
已踩过<
评论
收起
你对这个回答的评价是?
推荐律师服务:
若未解决您的问题,请您详细描述您的问题,通过百度律临进行免费专业咨询